Matrilin-1 is essential for zebrafish development by facilitating collagen II secretion - Neacsu, Cristian Dan; Ko, Ya-Ping; Tagariello, Andreas; Karlsen, Kristina Rokenes; Neiss, Wolfram Friedrich; Paulsson, Mats; Wagener, Raimund (Journal of Biological Chemistry, 2014)
Matrilin-1 is the prototypical member of the matrilin protein family and is highly expressed in cartilage. However, gene targeting of matrilin-1 in mouse did not lead to pronounced phenotypes. Here we used the zebrafish as an alternative model to study matrilin function in vivo. Matrilin-1 displays a multiphasic expression during zebrafish development. In an early phase, with peak expression at about 15 h post-fertilization, matrilin-1 is present throughout the zebrafish embryo with exception of the notochord. Later, when the skeleton develops, matrilin-1 is expressed mainly in cartilage. Morpholino knockdown of matrilin-1 results both in overall growth defects and in disturbances in the formation of the craniofacial cartilage, most prominently loss of collagen II deposition. In fish with mild phenotypes, certain cartilage extracellular matrix components were present, but the tissue did not show features characteristic for cartilage. The cells showed endoplasmic reticulum aberrations but no activation of XBP-1, a marker for endoplasmic reticulum stress. In severe phenotypes nearly all chondrocytes died. During the early expression phase the matrilin-1 knockdown had no effects on cell morphology, but increased cell death was observed. In addition, the broad deposition of collagen II was largely abolished. Interestingly, the early phenotype could be rescued by the co-injection of mRNA coding for the von Willebrand factor C domain of collagen II?1a, indicating that the functional loss of this domain occurs as a consequence of matrilin-1 deficiency. The results show that matrilin-1 is indispensible for zebrafish cartilage formation and plays a role in the early collagen II-dependent developmental events.
EVALuna2:9239